Modern Ideas About the Pathogenesis of Generalized Periodontitis - Muratova Saodat Kadirovna (Genius Journals, 2023)
In the article, studies on the problem of the etiology and pathogenesis of periodontal diseases using biochemical, histomorphological, immunological, hormonal, radiological and other research methods made it possible to view and clarify a number of pre-existing views on the causes and mechanism of periodontitis, which allows not on ыяly to conduct earlier and earlier studies accurate diagnosis of these diseases, but also to carry out more effective treatment, to outline effective methods of prevention. The analysis of modern domestic and foreign literature allows us to conclude that inflammatory and destructive periodontal diseases are a socially significant and general medical problem due to the high prevalence of pathology among all age groups of the population
Keywords: chronic generalized periodontitis; treatment; prevention